PATIENT TRUST ON THE HOSPITAL SERVICE DELIVERY SYSTEM - Abdul Haeba Ramli (Universitas Trisakti, 2016)
This research was conducted in 2016 to see the effect of the service delivery system on patient trust in private hospitals in Makassar. The number of patients used as respondents was 115 people, taken using purposive sampling technique, with several criteria set by the author. However, the results of this study indicate that a service delivery system consisting of contact personal and physical support has a positive and significant effect on patient trust